Democratic Republic of the Congo : Poverty Reduction Strategy Paper-Progress Report. (IMF Staff Country Reports; Country Report ;, 2010)
The Growth and Poverty Reduction Strategy was implemented in an extremely challenging environment, adversely affecting the conduct of macroeconomic and sector policies. The accomplishments in regard to sector policies are highly encouraging. There was notable progress in the administration of justice and police reform efforts. However, there were no significant developments in public administration reform. Congo recognizes that continued, sustainable growth in a stable macroeconomic climate is essential to reducing poverty, and this requires consolidating peace and security, and promoting administrative and economic governance.